Revisiting the Heavy Rainfall Event over Northern Taiwan on 3 June 1984 - Chih-Ying Chen; Yi-Leng Chen; Ching-Sen Chen; Pay-Liam Lin; Che-Ling Liu (Terrestrial, Atmospheric and Oceanic Sciences, 2013)

(untitled)
In this study, the mechanisms for the development of a localized heavy rainfall event during the evening of 2 June to the early morning of 3 June 1984 over northern Taiwan are investigated. This event occurred under favorable large-scale conditions including: upper-level divergence; low-level high equivalent potential temperature; low levels of free convection; and subsynoptic-scale ascending motion over the northern Taiwan Strait and northern Taiwan associated with a baroclinic front. In the late night of 2 June, pre-existing rainfall is simulated to the southeast of a trough axis over the southeastern China coast as well as in the frontal zone north of Taiwan. The pre-existing rainfall is enhanced as it moves over the northeastern Taiwan Strait where the prevailing southwesterly winds within the Taiwan Strait converge with the orographically deflected flow with a southerly wind component off the western/northwestern Taiwan coast. As the pre-existing convective rainfall continues to move toward northern Taiwan, it is further enhanced in a localized low-level convergence zone over the northwestern coast where a barrier jet along the coast converges with the northwesterly winds behind the surface front. Furthermore, on the morning of 3 June, focusing of rainfall is simulated where the barrier jet encounters the leading edge of the cold pool caused by rain evaporative cooling. As the convective rainfall areas drift inland, the orographic lifting of the pre-frontal southwesterly flow over the slopes south of the Taipei Basin also plays a role in the simulated enhanced heavy rainfall there.